2008
DOI: 10.1016/j.cortex.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between egocentric and allocentric visuospatial and tactile neglect in acute stroke

Abstract: Previous investigations provide evidence for distinction between egocentric (viewer-centered) and allocentric (stimulus- or object-centered) hemispatial neglect. However, it has not been determined whether this dissociation is modality-independent or modality-specific. We identify the incidence of egocentric and allocentric neglect in visual and tactile modalities, as well as the frequency of their co-occurrences in each modality. One-hundred patients with acute, right supratentorial ischemic stroke were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 49 publications
5
52
1
2
Order By: Relevance
“…It was speculated whether this obvious distinction between egocentric and object-based inattention separates neglect into body-and object-based forms (e.g., Marsh & Hillis, 2008;Hillis et al, 2005;Walker, 1995;Marshall & Halligan, 1993). In line with this notion, several anatomical studies carried out in neglect patients reported evidence for separate neural structures involved in egocentric versus object-based visual information processing (Medina et al, 2009;Grimsen, Hildebrandt, & Fahle, 2008;Rorden, Fruhmann Berger, & Karnath, 2006;Hillis et al, 2005;Binder, Marshall, Lazar, Benjamin, & Mohr, 1992).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was speculated whether this obvious distinction between egocentric and object-based inattention separates neglect into body-and object-based forms (e.g., Marsh & Hillis, 2008;Hillis et al, 2005;Walker, 1995;Marshall & Halligan, 1993). In line with this notion, several anatomical studies carried out in neglect patients reported evidence for separate neural structures involved in egocentric versus object-based visual information processing (Medina et al, 2009;Grimsen, Hildebrandt, & Fahle, 2008;Rorden, Fruhmann Berger, & Karnath, 2006;Hillis et al, 2005;Binder, Marshall, Lazar, Benjamin, & Mohr, 1992).…”
Section: Introductionmentioning
confidence: 91%
“…Egocentric and object-based mechanisms also seem to be involved in the disturbed spatial orienting behavior observed in stroke patients suffering from right hemisphere damage and spatial neglect. The characteristic failure of neglect patients to explore the side contralateral to the lesion has been described to occur not only with respect to egocentric reference frames but also relative to object-based coordinates (Savazzi, Mancini, Veronesi, & Posteraro, 2009;Marsh & Hillis, 2008;Hillis et al, 2005;Behrmann & Geng, 2002;Ota, Fujii, Suzuki, Fukatsu, & Yamadori, 2001;Behrmann & Tipper, 1994, 1999Karnath, Niemeier, & Dichgans, 1998;Pavlovskaya, Glass, Soroker, Blum, & Groswasser, 1997;Tipper & Behrmann, 1996;Behrmann & Moscovitch, 1994;Driver, Baylis, Goodrich, & Rafal, 1994;Karnath, 1994;Arguin & Bub, 1993;Driver, Baylis, & Rafal, 1992;Young, Hellawell, & Welch, 1992;Driver & Halligan, 1991;Gainotti, Messerli, & Tissot, 1972).…”
Section: Introductionmentioning
confidence: 98%
“…Este dado encontrado no estudo atual, corrobora com o estudo de Marsh et al 22 ., 2008. Os autores argumentam que podem existir diferentes regiões cerebrais com papéis específicos na computação de modalidades visuoespaciais 22 . Apenas o tálamo foi acometido em indivíduos de ambos os grupos no estudo atual.…”
Section: Resumo | Introduçãounclassified
“…Apenas o tálamo foi acometido em indivíduos de ambos os grupos no estudo atual. Em estudo realizado com heminegligentes com a região talâmica acometida, os autores afirmam que lesões no tálamo estão fortemente associadas à heminegligência, principalmente no núcleo pulvinar, que está envolvido na exploração e orientação da atenção no espaço 22 .…”
Section: Resumo | Introduçãounclassified
“…The second stage of recovery is the subacute phase and this lasts until six months post-stroke. Recovery during this period is less rapid and consists of neural reorganisation, specifically, the establishment of alternative networks, synaptic remodelling and axonal sprouting (Lazar & Antoniello, 2008;Marsh & Hillis, 2008). The last stage of recovery is the chronic phase and once this stage is reached, recovery will have slowed considerably.…”
Section: Stages Of Recoverymentioning
confidence: 99%